A Qualitative Analysis and Systematic Literature Review on Enhancing Maritime Vocational Education - Winarno; Riyanto; Barasa, Larsen; Kuntadi, Cris; Malau, April Gunawan; Herawati, Susi; Wibowo, Titis Ari; Simanjuntak, Marudut Bernadtua (Lembaga Einstein College (LEC), 2025)
This study examines the alignment between maritime vocational education and the evolving needs of the maritime industry, particularly focusing on sustainability, technological integration, and industry collaboration. Maritime education is vital for preparing professionals to handle the complexities of port and shipping management, deck and naval operations, and sustainable practices in maritime environments. The research combines qualitative analysis from interviews with ten participants—including maritime professionals, lecturers, and graduates—and a Systematic Literature Review (SLR). The objective is to assess how well current maritime education frameworks address industry demands and the integration of emerging concepts such as sustainability and technology. The findings indicate a strong alignment between education and industry needs, particularly in practical training and simulation-based learning. However, gaps persist in the practical application of sustainability concepts and the equitable distribution of technological resources. This study highlights the necessity of deepening collaborations between educational institutions and industry stakeholders to ensure that curricula reflect the latest industry trends and technological advancements. The research also calls for a more consistent application of sustainability principles in maritime training programs. By addressing these challenges, maritime education can significantly enhance graduate readiness and industry relevance. The insights offered have practical implications for educators, policymakers, and industry leaders seeking to improve the quality and impact of maritime vocational education.